Glucan-MOS® improved growth and innate immunity in pacu stressed and experimentally infected with Aeromonas hydrophila - Soares, Michelly Pereira; Oliveira, Fulvia Cristina; Cardoso, Israel Luz; Urbinati, Elisabeth Criscuolo [UNESP]; Meldau de Campos, Cristiane; Hisano, Hamilton (Elsevier, 2018)
We tested the efficacy of a commercial product (Glucan-MOS®) derived from yeast Saccharomyces cerevisiae, containing two combined products, β-1,3-1,6 glucans and mannans on the growth, feed efficiency, stress and innate immune responses of juvenile pacu (Piaractus mesopotamicus) after a stressful handling and bacterial inoculation. For this, we evaluated the serum cortisol and plasma glucose levels, the respiratory activity of leukocytes, the serum lysozyme levels, as well as the number of circulating erythrocytes and leukocytes of fish fed during 30 days with diets containing increased levels of Glucan-MOS (0.0, 0.1, 0.2, 0.4 and 0.8%). The supplementation of 0.1% improved weight gain, feed conversion and the protein efficiency ratio compared to a control diet. The 0.2 and 0.4% Glucan-MOS® diets were sufficient to increase the respiratory burst of leukocytes and lysozyme activity, the number of thrombocytes, neutrophils and monocytes in the blood after a stressful handling and bacterial challenge, and minimized stress response as shown by decreased cortisol and glucose levels when compared to the control. The results of this work reinforce the benefits of the adoption of feeding strategies including combination of both β-1,3-1,6 glucans and mannans as a dietary supplement in periods prior to intensive management. The 30-day period was sufficient to stimulate growth performance, improve nutrient utilization, minimize stress response and modulate innate immunity responses.
Keywords: Bacterial challenge; Handling; Immunostimulants; Mannan; Stress; β-1,3-1,6 glucans